The Implementation of the Jigsaw Cooperative Learning Model on the Topic of Measures of Central Tendency in Grade VIII of SMP Negeri 3 Jayapura - Sirampun, Elsi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the implementation of the Jigsaw type cooperative learning model in the topic of Measures of Central Tendency in Class VIII B of SMP Negeri 3 Jayapura in the 2024/2025 academic year. This research is a descriptive study using a qualitative approach. The subjects were determined through purposive sampling, consisting of 18 students from Class VIII B. Data were collected through tests and observations.The implementation of the Jigsaw cooperative learning model in teaching Measures of Central Tendency was carried out very well. This is evidenced by the observation score of 81.5%, indicating a high level of implementation. Student activeness was also high, with an observation result of 81,8%, showing that students were very active during the learning process. Furthermore, the students’ learning outcomes showed an average score of 75.4, with 13 students meeting the Minimum Mastery Criteria (KKM) and 5 students not meeting the criteria.